Advances in Knowledge Discovery and Data Mining 15th Pacific-Asia Conference, PAKDD 2011, Shenzhen, China, May 24-27, 2011, Proceedings, Part II - Huang, Joshua Zhexue; Cao, Longbing; Srivastava, Jaideep; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNAI 6634 and 6635 constitutes the refereed proceedings of the 15th Pacific-Asia Conference on Knowledge Discovery and Data Mining, PAKDD 2011, held in Shenzhen, China in May 2011. The total of 32 revised full papers and 58 revised short papers were carefully reviewed and selected from 331 submissions. The papers present new ideas, original research results, and practical development experiences from all KDD-related areas including data mining, machine learning, artificial intelligence and pattern recognition, data warehousing and databases, statistics, knoweldge engineering, behavior sciences, visualization, and emerging areas such as social network analysis.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Algorithm Analysis and Problem Complexity; Computer Communication Networks